Effects of acetaminophen on mitochondrial complex I activity in the rat liver and kidney: a PET study with (18)F-BCPP-BF - Ohba, Hiroyuki (EJNMMI Res, 2016)
BACKGROUND: In the present study, 2-tert-butyl-4-chloro-5-[6-(4-(18)F-fluorobutoxy)-pyridin-3-ylmethoxy]-2H-pyridazin-3-one ((18)F-BCPP-BF), a PET probe for mitochondrial complex I (MC-I), was used to validate whether MC-I is a useful biomarker for detecting acetaminophen-induced dysfunctions in the liver and kidney. The kinetic and distribution of (18)F-BCPP-BF were assessed in rats using high-resolution animal PET in vivo. The binding specificity of (18)F-BCPP-BF to MC-I in the liver and kidney was confirmed by the pre-administration of rotenone, a specific MC-I inhibitor. The effects of acetaminophen on MC-I activity were assessed 2 and 24 h after the administration of vehicle or acetaminophen at a dose of 100 or 300 mg/kg. Biochemical parameters in plasma and urine were assessed 2, 6, and 24 h after the administration of vehicle or acetaminophen. RESULTS: The uptake of (18)F-BCPP-BF by the liver and kidney was significantly inhibited by the pre-administration of rotenone. Two and more hours after the administration of acetaminophen, the uptake of (18)F-BCPP-BF was dose-dependently reduced in the liver, even at 100 mg/kg, and in the kidney at 300 mg/kg, whereas biological parameters started to be affected 6 h or later at doses of 300 mg/kg. CONCLUSIONS: The present study demonstrated that (18)F-BCPP-BF has potential as a PET probe for the quantitative imaging of hepatic and renal dysfunction as impaired MC-I activity in the early phase of the treatment for an overdose of acetaminophen in the living body with PET.